Mediating role of financial behavior between financial factors and economic well-being: through the lens of the extended family resource management model - Wijekoon, Rusitha; Sabri, Mohamad Fazli; Ahmad, Nobaya; Abd Rahim, Husniyah (Human Resource Management Academic Research Society, 2022)
The major aim of this study is focused on assessing the direct, and indirect factors that affect individuals’ economic well-being. The multistage random sampling was utilized to choose the sample of the coconut growers in Sri Lanka. The data were analyzed by PLS-SEM in Smart-PLS. All the direct relationships between the determinants of economic well-being (financial behavior, financial knowledge, money attitude), and economic well-being were revealed significant, and their impact was positive. All together 88.9% of the total variance of economic well-being was explained by the three variables. Moreover, the impact of money attitudes, and financial knowledge on financial behavior was also examined. But, only money attitude, and financial behavior association was confirmed, and 78.2% of variance in financial behavior was clarified. The financial behavior was further hypothesized as a mediator between financial knowledge, money attitude, and economic well-being, but only money attitude, and economic well-being relationship was mediated by the financial behavior. The current study widens our understanding of financial factors, and their impact on economic well-being, and coconut growers, academicians, and policy makers can use this knowledge to avoid barriers, address the research gaps in the context of family economics and management, and design policy guidelines.